Examination of social studies teacher candidates’ views on digital citizenship - Ayşegül Çelik Geldi; Ebru Kamiş (Institute of Advanced Engineering and Science, 2026)
This research aims to reveal prospective teachers’ understanding of the concept of digital citizenship. This study utilized a qualitative research model, employing phenomenological design to identify pre-service teachers’ understanding of digital citizenship. The study group consisted of 100 prospective teachers enrolled in the Social Studies Education Department of the Faculty of Education at a university in Türkiye during the 2025-2026 academic year, selected according to convenient sampling. A semi-structured interview form consisting of five questions was prepared. Content analysis was used in the analysis of the study’s data. Based on the research findings, it was determined that prospective teachers defined digital citizenship, digital ethics, digital security, digital bullying, and digital literacy. Finding reveal that participants defined digital citizenship across dimensions such as digital literacy, ethics, security, bullying and identity, though often superficially. Results indicate partial awareness but limited competencies, highlighting the need to strengthen teacher education programs in digital citizenship.